Pemahaman Teologi Islam Bagi Pecandu Narkoba Dalam Perilaku Agama dan Sosial - Budi Harianto (UIN Sumatera Utara, 2022)
Drugs are something that is inserted into the body, drugs spread like bacteria that can attack anyone, young or old, rich or poor, even today, many teenagers who fall into this are from harmonious families. In this analysis, the author proposes a theoretical approach which includes: Understanding theology in general, Definition of Drugs, Drugs in the view of Islam, Types of Drugs, Consequences of Drug Abuse, Drug Countermeasures, and Legal Basis for Drug Abuse that regulates it. Furthermore, the author puts forward an understanding of the Islamic Theology of Drug Addicts which includes the factors that cause drug addicts, Drug Addicts' Belief in God's Actions and Human Actions, and Drug Addict's Views on the Concept of Faith, Reward and Sin. The researcher's review of the understanding of Islamic theology for drug addicts in social and religious behavior, based on the existence of religious knowledge taught both by their families and by religious leaders, is still limited to religious knowledge possessed by ordinary people, it is proven that the way of understanding is still related to reason. and revelation.